(untitled) (International Journal of Health, Animal Science and Food Safety, 2018)
Water buffaloes mastitis represents a major issue in terms of animal health, cost of therapy, premature culling and decreased milk yeld. The emergence of antibiotic resistance has led to investigate strategies in order to avoid or minimize the antibiotic use, especially during subclinical mastitis disease (SM) (1). Lactobacillus rhamnosus is part of the normal gut microflora, having meanwhile an immunostimulatory activity (2). The aim of this study was to investigate the change of milk microbiota after the theraputic treatment with inactivated cultures of Lactobacillus rhamnosus of mammary gland quarters affected by subclinical mastitis. A number of 43 quarters were included in the study, and were treated with antibiotics, Lactobacillus rhamnosus and PBS as negative control. Samples were collected at two time points, T0 and T5 (days) and V4 region of 16S rRNA gene was amplified by PCR and sequenced using Ion Torrent Personal Genome Machine. The microbiota structure of SM quarters showed no major changes after PBS treatment, while differed after antibiotic treatment where Staphylococcus decreased its relative abundance from 41% at T0 to 3% at T5. Lactobacillus rhamnosus induced a less dramatic change in milk microbiota, although the relative abundance of some genera were found to be modifidied, among which an increase of Pseudomonas from 1.5% at T0 up to 4% at T5. No differences were present between the microbiota structure of quarters treated with Lactobacillus rhamnosus and PBS. This study allowed to characterize the changes of microbiota in milk from animals with Lactobacillus rhamnosus and antibiotics. While changes in milk microbiota after antibiotic treatment were evident, changes after Lactobacillus rhamnosus were more limited. Further investigations are needed to evaluate alternative strategies to mastitis treatment.